1991
DOI: 10.1016/0014-5793(91)80711-b
|View full text |Cite
|
Sign up to set email alerts
|

Pyrophosphate‐dependent phosphofructokinase, an anaerobic glycolytic enzyme?

Abstract: Recent evidence indicates that in as diverse organisms as unicellular eukaryotes, higher plants and prokaryotes, anaerobic glycolysis relies on a pyrophosphate-dependent phosphofructokinase instead of the classical ATP-dependent enzyme. This difference in phosphoryl donor specificity does not necessarily reflect a primitive metabolism, as thought earlier, but could rather be the result of convergent evolution, fostered by the energetic advantage conferred to the cell when glycolysis is the sole source of ATP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(110 citation statements)
references
References 27 publications
3
105
1
Order By: Relevance
“…PP, levels do not alter detectably during rapid changes in the rate of respiration or when tissues are subjected to anoxia or respiratory poisons (Dancer and ap Rees, 1989;Quick et al, 1989) whereas ATP levels change appreciably under these conditions. Since other PP,-linked enzymes, such as PP, :phosphofructokinase, are induced by anoxia in plants (Mertens et al, 1990), it has been suggested that the coordinate stabilization of PP, levels and operation of the V-PPase and other PP,-dependent enzymes would provide a back-up system for metabolism during anaerobiosis (Mertens, 1991 ;Rea and Poole, 1993). Indeed, the capacity of the V-PPase for primary H i -translocation may confer a double advantage during anaerobiosis.…”
Section: Discussionmentioning
confidence: 99%
“…PP, levels do not alter detectably during rapid changes in the rate of respiration or when tissues are subjected to anoxia or respiratory poisons (Dancer and ap Rees, 1989;Quick et al, 1989) whereas ATP levels change appreciably under these conditions. Since other PP,-linked enzymes, such as PP, :phosphofructokinase, are induced by anoxia in plants (Mertens et al, 1990), it has been suggested that the coordinate stabilization of PP, levels and operation of the V-PPase and other PP,-dependent enzymes would provide a back-up system for metabolism during anaerobiosis (Mertens, 1991 ;Rea and Poole, 1993). Indeed, the capacity of the V-PPase for primary H i -translocation may confer a double advantage during anaerobiosis.…”
Section: Discussionmentioning
confidence: 99%
“…PFP appears to be an adaptive enzyme whose activity is responsive to environmental stresses, such as Pi nutrition and anaerobiosis, and to developmental or tissue-specific cues (Duff et al, 1989b;Stitt, 1990;Mertens, 1991;Theodorou et al, 1992). Unlike plant PFK, most plant PFPs display potent activation by nanomolar concentrations of the regulatory metabolite Fru-2,6-Pz (Stitt, 1990).…”
Section: Pfp a N Adaptive Enzymementioning
confidence: 99%
“…The PFP of several heterotrophic plant tissues has also been proposed to operate as a glycolytic bypass to PFK during periods of anaerobiosis (Mertens, 1991). The use of PPi rather than ATP could confer a significant energetic advantage to plants subjected to environmental stresses, such as Pi deprivation or anoxia.…”
Section: Pfp a N Adaptive Enzymementioning
confidence: 99%
“…In addition, effectors that modulate the activity of PFK in other organisms, such as ATP, citrate, fructose 2,6-bisphosphate and P i , have no effect in Trypanosoma brucei (Michels et al 1997) or Leishmania donovani (Lopez et al 2002). The many differences between the active site of the two classes of PFKs and the striking differences in ligand-binding properties between the human and parasite enzymes suggest great potential for structure-based design of drugs (Mertens 1991, Michels et al 1997). In a previous biochemical characterisation of Trypanosoma cruzi PFK (Aguilar & Urbina 1986), this enzyme was reported to have an apparent molecular mass of 17,000 and a complex kinetic pattern for its interaction with D-F6P.…”
mentioning
confidence: 99%